Population dynamics of Meloidogyne graminicola and Hirschmanniella oryzae in a double rice-cropping sequence in the lowlands of Myanmar - Win, Pa Pa; Kyi, Pyone Pyone; Maung, Zin Thu Zar; De Waele, Dirk (Brill, 2013)
The rice root-knot nematode, Meloidogyne graminicola, and the rice root nematode, Hirschmanniella oryzae, are considered potentially important nematode pathogens in lowland rice. A study was undertaken from December 2009 until December 2010 in the Ayeyarwady River Delta, the major lowland rice-producing area of Myanmar, to monitor the population dynamics of M. graminicola and H. oryzae in a naturally infested field. Root samples of the two rice varieties Yatanartoe and Taungpyan that are commonly cultivated in double rice-cropping sequences in Myanmar and represent irrigated and rainfed lowland rice varieties, respectively, were obtained for nematode analysis. During the summer-irrigated rice-growing season the root population density of second-stage juveniles (J2) of M. graminicola showed two distinct peaks – at the maximum tillering stage of the rice plants in January and at the heading stage of the rice plants in March 2010. With the onset of the monsoon rains, the J2 population densities in the roots of ratoon rice plants gradually decreased in May. During the rainfed monsoon rice-growing season, very low population densities of M. graminicola J2 were detected in the roots of rice plants, while the root population density of H. oryzae juveniles and adults showed two distinct peaks – at the maximum tillering stage of the rice plants in August and at the heading stage of the rice plants in October 2010. With the onset of the dry season, population density of H. oryzae in the roots reached the lowest density at harvest in November. Root galling caused by M. graminicola followed the same trend as the J2 population densities throughout the irrigated season. No root galls were observed during the monsoon season. Our results can be used for practical purposes aimed at a better management of both M. graminicola and H. oryzae.